PENGARUH PENGARUH PARAMETER PADA PROSES 3D PRINTING MENGGUNAKAN FILLAMENT EAL-FILL TERHADAP AKURASI DIMENSI DAN KEKERASAN DENGAN PENDEKATAN METODE TAGUCHI - Icvan Apriansyah; AHMAD ZAMHERI; FATAHUL ARIFIN (Machine : Jurnal Teknik Mesin, 2021)
The presence of 3D printing technology in the world of manufacturing has brought big changes to the world. This technology, which is also known as Additive Layer Manufacturing, has actually been around since the 1980s. The emergence of 3D Printing technology is very influential in several industrial fields. Therefore this study was carried out to find out and increase knowledge about the eAl-fill fillament which will be tested using dimensional accuracy and hardness testing on the fillament using the Taguchi method.From the analysis of variance (ANOVA) states that the parameter that has the most influence on the dimension of accuracy is the layer height with a contribution value of 64.233%. Meanwhile, the most influential parameter of hardness is the print temperaure with a contribution value of 41.929%.